The effects of TiO2 nanoparticles on the temperature-dependent electrical and dielectric properties of polypropylene - Zhang, Hao; Duan, Yubing; Xie, Maojie; Ma, Guoqing; Li, Pengfei; Qin, Jiafeng (Frontiers in Energy Research, 2022)
Nanoparticles are found to have capacity to improve the specific properties of polypropylene (PP) for recyclable cable insulation material. However, previous studies have focused on the modification effect at room temperature, and few studies on the nano-modification effect under high temperature environment. This paper aims to study the effect of nanoparticle electrical and dielectric properties of PP at different high temperature. Both TiO2 nanoparticles and PP/TiO2 nanocomposite samples are prepared in laboratory by wet chemical method and surface modification. Then the AC and DC breakdown strength, conductivity, permittivity and dielectric loss of PP/TiO2 nanocomposite are measured at different temperature. The results show that TiO2 nanoparticles introduce amount of charge traps into PP to restrain the conductivity and improve the breakdown strength of PP. But due to the additional interfacial polarization between TiO2 nanoparticles and PP matrix, the permittivity and dielectric loss of PP/TiO2 nanocomposite are enhanced, especially at low frequency.